A New Face Subunit Transplant Model in Mice, Containing Skin, Mandible, and Oral Mucosa for Future Face Vascularized Composite Allotransplantation Studies. Issue 1 (July 2019) - Cardona, Esteban; Wang, Aline Yen Ling; Loh, Charles Yuen Yung; Chuang, Sheng-Hao; Lee, Chin-Ming; ALDeek, Nidal; Lin, Cheng-Hung; Wei, Fu-Chan
Abstract : Background: In immunologic research, mice have advantages over other animals, such as low costs, easy handling, suitable life cycle, and adequate laboratory resources. However, vascularized composite allotransplantation surgery using mice is not popular, partly because of technical difficulties and high mortality rates. The authors' goal was to demonstrate a face transplantation model in mice that includes skin, mandible, and oral mucosa. Methods: The authors developed a new syngeneic face transplantation model composed of skin, mandible, teeth, and oral mucosa in C57BL/6 mice. The following assessment included measuring the length of the right incisor on the transplanted mandibles, computed tomographic scan in one mouse for mandibular structure evaluation, and histologic examination of different tissue samples in another mouse for viability evaluation. Results: The authors performed five consecutive transplantations. The donor vessels were the common carotid artery (approximately equal to 0.4 mm) and the anterior facial vein (approximately equal to 0.2 mm), and the recipients were the common carotid artery and the posterior facial vein (approximately equal to 0.4 mm). The mean operative time was 80 minutes for the donor and 123 minutes for the recipient. There were neither flap failures nor animal deaths. The follow-up was 6 months. The right incisor of the transplant grew at different rates in all cases. Histologic samples showed viability in all tissues, including mandibular bone marrow. Computed tomography demonstrated normal structure of the transplanted bone. Conclusion: The authors' syngeneic partial face transplantation model in mice, which included skin, oral mucosa, and mandible with teeth, should be useful for future face allotransplantation research, as the myriad of tissues it provides, of different immunomodulatory functions, is similar to that in the clinical scenario. Abstract : Supplemental Digital Content is available in the text.